A Marketer’s Point of Views: Strategy of Developing and Reinforcing Brand Loyalty In The 1990’s - Anas Hidayat (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2005)
The rapid change in competition and technology results in decrease in brand loyalty and business decline. This means that keeping customer loyalty is a very challenging effort today because brand loyalty is very important to acquire, maintain, and develop market share. To keep customer loyal to a certain brand or to keep a brand valuable in front of the customers’ eye, marketer must be able to reduce marketing cost, to maintain trade leverage, to attract new customers, and to provide time to respond to competitive trade. Strategies that support to gain and retain the loyalty of today’s consumers are understanding the customers, keeping brand image consistent, running promotion that develop loyalty, maintaining high standards of customer service, and soliciting retailer participation. Nevertheless, even for the company who has strong brand, reinforcing brand loyalty is still needed. There are seven factors that will relate to build brand loyalty reinforcement.Key words: customer or brand loyalty.